Literature review Penggunaan Computerized Cognitive Behavioural Therapy (CCBT) Pada Pasien Depresi - Tiveni Elisabhet (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2020)
Introduction: Industrial advancement in the current technological era greatly affects aspects of life without exception in the field of health, especially in nursing. Nursing is required to be more innovative in treating patients. Computerized Cognitive Therapy (CCBT) is one of the computerization-based programs to treat patients with depression. Method: This study uses a literature review that focuses on Computerized Cognitive Therapy (CCBT). This review literature consists of nine international journals through the Online database (ScienceDirect, Clinical Key, Elsevier since 2015-2020). Results: The use of CCBT showed significant improvement in depressed patients, especially in improving mood and in the verbal behavior of patients. Conclusion: CCBT makes the treatment assistance process unlimited by space and time and CCBT becomes one of the additional treatment alternatives for depression. Kata Kunci : Depression, Cognitive Behavioural therapy of Depression, Internet Cognitive Behaviour Therapy (ICBT)